2013
DOI: 10.1515/wpsr-2012-0014
|View full text |Cite
|
Sign up to set email alerts
|

Towards a Representative Bureaucracy: Promoting Linguistic Representation and Diversity in the Swiss and Canadian Federal Public Services

Abstract: Drawing on the concept of representative bureaucracy, this article examines how two multilingual states -Canada and Switzerland -deal with issues related to the participation of different linguistic communities in the federal public service. Following a political mobilization of the linguistic cleavage, strategies to promote multilingualism in the public service have been adopted in both countries. The Canadian strategy focuses on equal treatment of Anglophones and Francophones in the public service. In Switze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…The coexistence of the sub‐national cultures and language regions has a long tradition in the country's identity. In the federal administration most meetings are bilingual, provided there is sufficient proficiency (Kübler et al ). Thus, passive multilingualism and conversation in two or three languages is customary in Swiss public administration.…”
Section: The Study Settingmentioning
confidence: 99%
See 2 more Smart Citations
“…The coexistence of the sub‐national cultures and language regions has a long tradition in the country's identity. In the federal administration most meetings are bilingual, provided there is sufficient proficiency (Kübler et al ). Thus, passive multilingualism and conversation in two or three languages is customary in Swiss public administration.…”
Section: The Study Settingmentioning
confidence: 99%
“…In the federal administration most meetings are bilingual, provided there is sufficient proficiency (Kübler et al 2013). Thus, passive multilingualism and conversation in two or three languages is customary in Swiss public administration.…”
Section: 'Peace Of Languages' Through Informal Strategies and Passimentioning
confidence: 99%
See 1 more Smart Citation
“…These are also the variables most commonly investigated by representative bureaucracy scholars. Recent studies have indicated that additional individual characteristics (e.g., age, disability, sexual orientation, veteran status, and language) should also be considered (Gade & Wilkins, 2013;Kelly, 1998;Kübler et al, 2012;Lewis & Ng, 2013;Slack, 2001;Thielemann & Stewart, 1996). Additionally, level of education and party identification have been shown to affect bureaucrats' selfperceptions as minority representatives (Selden et al, 1998).…”
Section: Passive and Active Representative Bureaucracymentioning
confidence: 99%
“…Most of these studies explored the factors that influence the attitude, values, and behavior of minority bureaucrats and eventually drive them to become active representatives of their minority group. These factors include demographic variables such as sex, race, ethnicity, sexual orientation, veteran status, language, and political affiliation (Gade & Wilkins, 2003;Kelly, 1998;Kübler, Kobelt, & Andrey, 2012;Selden, Brudney, & Kellough, 1998;Slack, 2001). Researchers have also explored how minority bureaucrats are influenced by organizational factors, such as length of time working in the public sector, perceived work obligations, the organizational environment, the issue to be considered, organized employee groups, the bureaucrat's position in the organizational hierarchy and the physical location of the bureaucrat's office in the entity (Selden et al, 1998;Thompson, 1976).…”
Section: Introductionmentioning
confidence: 99%